PENGARUH PEMBERIAN SUMBER NITROGEN DAN BIBIT BAKTERI ACETOBACTER XYLINUM TERHADAP KUALITAS HASIL NATA DE TALA - Musdawati Parma Safitri; Muhammad Wiharto Caronge; Kadirman Kadirman (Universitas Negeri Makassar, 2017)
The Purpose of this research is to know the effect of using nitrogen sources and medium starter in the making of nata on the rendemen, fiber content as well as the organoleptic of nata based on conformance of nata SNI standards. Method of this research using a randomized block design (RAK) factorial with 2 factors. The first factor, source nitrogen using urea mung bean sprouts and soybean sprouts. The second factor is medium starter with using coconut water and nira tala. The data analyzed by using ANOVA technique with further Duncan experiment. The result of the experiment showed that the best nata is produced from the use of nitrogen sources soybean sprouts and starter nira tala.